Effect of phytase and FYM on soil enzyme activities, microbial population and nutrient availability of non-calcareous soil - Jadhav, A.B.; Suradkar, R.; Taggu, B.; Tamboli, B.D.; Priyanka, B. (Journal of the Indian Society of Soil Science, 2017)
A pot culture experiment was conducted to assess the effect of phytase and FYM levels on soil enzyme activities and nutrient availability of non-calcareous soil under soybean cultivation. The treatment consisted of four levels of phytase (0, 1200, 2400 and 3600 IU) and FYM (0, 2.5, 5.0 and 7.5 t ha-1). Enzyme activities and nutrient availability in soil was assessed at 50% flowering and harvest of soybean. It was observed that application of phytase @ 3600 IU recorded significantly higher acid and alkaline phosphatase and dehydrogenase activity at both the growth stages of soybean. Results revealed that significant interaction effect with combine application of phytase @ 3600IU and FYM @ 7.5 t ha-1 recorded higher bacterial, fungal and actinomycetes population. Combined application of phytase @ 3600 IU and FYM @ 7.5 t ha-1 recorded significantly higher available nitrogen (289.3 and 213.6 kg ha-1) and potassium (295.0 and 270.6 kg ha-1) at 50% flowering and at harvest of soybean, respectively. However, in case of phosphorus (P), at 50% flowering significantly higher available P was recorded with phytase @ 3600 IU + 7.5 t ha-1 (23.9 kg ha-1). Reduction trend obtained for calcium carbonate content from 4.24 to 3.68% at 50% flowering and from 4.20 to 3.60% at harvest stage was obtained with the application of phytase @ 3600 IU. This study suggest that application of phytase in combination with manure substantially improves soil biological activities as well as better nutrient supply to crop.